The Reliability of Bonding between Alumina-Pure Metals Through Diffusion Mechanism - Jabbar, Thamir A; Sarkis, Zareh A; Nagie, Arwa G (Al-Nahrain Journal of Science, 2013)
Bonding between dissimilar materials such as alumina to metals by diffusion mechanism was investigated in this work. Foils of high purity metals (Silver, Copper, Zinc, Aluminum, Lead and Tin) have been prepared with 1mm thickness and area of 1cm x 1cm. The foils have then be placed between two alumina blocks of similar area and 0.5cm thickness as a sandwich panel. Bonding has been achieved by using a suitable fixing under pressure of 0.3 MPa and then heated to about 90% of the melting point temperature of each investigated metals for 2 hours as a socking time in an atmospheric condition. For evaluation the bonding strength of fabricated joints, tensile test technique was used for this purpose. Three categories of bonding strength were obtained but the upper value of joint strength obtained is 86.5x104Pa of the joint involved silver and tin metals. Obviously three types of fracture surfaces were obtained; fracture in alumina part, fracture in the interface region and fracture in metal part. Fracture surfaces were attempted by NDT (non destructive test) using optical microscope and x-ray techniques. Due to reduction of surface and bulk diffusivity an oxidation layers which covered the contact surfaces was found effected parameters caused to reduce the diffusivity and followed bonding strength of the fabricated joints.